Comparative Benchmarking Of Constraints T-Way Test Generation Strategy Based On Late Acceptance Hill Climbing Algorithm - Kamal Z., Zamli; Alsewari, Abdulrahman A.; Al-Kazemi, Basem (Penerbit UMP, 2015)
This paper describes the new t-way strategy based the Late Acceptance based Hill Climbing algorithm, called LAHC, for constraints t-way test generation. Unlike earlier competing work, LAHC does not require significant tuning in order to have it working. In fact, LAHC merely requires minor adjustment of the common controlling parameters involving iteration and population size depending on the given system configuration. Our benchmarking results have been promising as LAHC gives competitive results in most constraints configurations considered.